DAYA DUKUNG KAWASAN PERDESAAN UNTUK PENGEMBANGAN WISATA BAHARI - Edy Said Ningkeula; M. Chairul Basrun Umanailo; Sofian Malik; Iskandar hamid; Rosita Umanailo (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
The purpose of this study is to get a primary picture of the carrying capacity of rural areas on the West coast of Buru Island for the development of marine tourism in Buru Regency. The research will be conducted by taking samples in 3 Subdistricts namely Liliali Waplau and Airbuaya where the entire village is located on the North West coast of Buru Island and has the potential and richness of marine biota that has not been fully explored. The approach used in this study uses a qualitative approach and the number of informants to be interviewed is 20 people. For sampling techniques, researchers use stratified random sampling, which takes samples from the population by grouping them into several strata and then randomly selected from each group with the consideration that informants are considered as related parties to achieve the research objectives. This study uses data collection techniques or techniques that use observation, in-depth interviews to get data on the socio-economic conditions of the community, related to the implementation of the bupolo maghrib reciting. The analysis technique used in this study is qualitative data analysis following the concepts given by Miles and Huberman and Spradley. The results showed that coastal tourism activities by utilizing coastal and marine areas can be done directly or indirectly. The types of marine tourism that can be directly utilized on the West coast of Buru Island include boating, swimming, snorkelling, diving and fishing.